Case-based learning: Our experience in clinical pharmacology teaching - Hasamnis, Ameya; Arya, Aditya; Patil, Sapna (Journal of pharmacy & bioallied science, 2019)
Majority of junior doctors struggle to apply the knowledge of pharmacology to prescribing drugs. A paradigm shift in teaching of clinical pharmacology is the need of the hour in medical curriculum. One of the ways to enhance the teaching of clinical pharmacology is to develop and conduct case-based learning for MBBS students instead of didactic lecturing. Case-based learning session can bridge the gap between theory and practice. Case-based learning provides hands-on training in a classroom setting. We tried to develop and conduct case-based learning for year two medical students and evaluated their response via the Dundee Ready Education Environment Measure questionnaire. Majority of our students enjoyed learning clinical pharmacology through case-based learning. Case-based learning also provided students the opportunity to embrace the principles of problem solving, critical thinking, and lifelong learning. It helped students to amalgamate the concept of development of P drug list with rationale prescribing habits. Majority of our students also agreed that they understood the content of the subject taught in the session.